Influence of personality traits on people’s satisfaction with public service in Hanoi city, Vietnam - Tung, Phuong Huu; Ly, Le Thi Khanh (Linguistics and Culture Review, 2021)
The quality of public services is concerned and improved to meet the satisfaction of the people, which has made governments more aware of the need to provide public services according to the needs and preferences of the public. Most of the previous studies used qualitative methods to assess people’s satisfaction with public services. The authors use a quantitative research method to explore the quality of public services in Vietnam using the Servqual model and explore the relationship between personality traits and satisfaction with public services. The study was conducted in OSS rooms in Hanoi city, Vietnam in June 2021, using the intentional sampling method. Collect data through survey of 500 votes, of which 350 valid votes of citizens. The results of analysis by SEM model show that all 5 elements of personality traits: Openness, Dedication, Neuroticism; psychic; Greablenes has a positive and significant influence on the remaining 5 factors through 2 coefficients, Regression Weights and P-value, both have reliable values. The conclusion of this study provides valuable data for Government policymakers.